Composição, recrutamento e potencialidade toxigênica de cianobactérias em um tributário do reservatório de Rosana, Paraná, Brasil. - Fonseca, Iraúza Arroteia (2008)
Cyanobacteria are an important component in plankton and periphyton communities. Our main object of study was the community of cyanobacteria, emphasising the periphyton. We conducted three studies, at first instance, aim to make the first taxonomic contribution on ficoflórula of periphytic cyanobacteria in a tributary of the Rosana reservoir, specifically in Corvo river, in mesocosms installed inside and outside of aquatic macrophytes stands. 87 taxa were identified, included in three orders: Oscillatoriales, with 59 taxa, Chroococcales, with 27 taxa and Nostocales, with two taxa. Evaluated through mesocosms installed inside and outside of aquatic macrophytes stands, the links between plankton and periphyton communities through directional migration, to better understanding the recruitment of cyanobacteria. In the first analysis, in mesocosms installed inside aquatic macrophytes stands, 47.2% of cyanobacteria recorded in the phytoplankton community were recruited from the periphytic community. For mesocosms installed outside banks of aquatic macrophytes, 27.3% of species showed recruitment. Through an analysis of co-occurrence, it was observed that the species of cyanobacteria are not randomly distributed in mesocosms installed inside aquatic macrophytes stands, ie species found co-occur together, the opposite were observed in mesocosms installed outside aquatic macrophytes stands. The Corvo river presents blooms of cyanobacteria Radiocystis fernandoi in certain seasons. These can be caused by recruitment. Thus, the amplification of mcyA gene can confirm the hypothesis that the bloom of Radiocystis fernandoi of Corvo river is a variety with positive genotype for microcystin. The samples collected in Corvo river showed positive results for the presence of the gene mcyA. Thus, we believe that (a) contributing to the knowledge of the composition of periphytic cyanobacteria, (b) showing the process of directional migration of this group for the plankton and (c) identifying the presence of positive genotype for microcystins in R. fernandoi by a simple technique with low cost, provide guidelines, and a useful tool for those who work for the government.